Retronasal Olfaction Stimulation and its Implication for Health: A Commentary on the Available Evidence. - Garduño-Diaz, Sara D. (European Journal of Applied Sciences, 2023)
Retronasal olfaction is the perception of odors emanating from the oral cavity during eating and drinking, as opposed to orthonasal olfaction, which occurs during sniffing (Rozin, 1982). The retronasal olfactory pathway contributes to the perceived flavor of foods and drinks. Retronasal and orthonasal function are distinct physiologic processes, with evidence identifying divergent neurobiological mechanisms (Small et al., 2005). A diminished quality of life has been reported from dysfunctions of both retronasal and orthonasal olfaction, especially when adversity occurs with the identification of food and drinks (Oleszkiewicz et al., 2019). Until recently, interest in retronasal olfaction extended only to food-related questions, with its clinical significance being limited to a means for detecting malingerers in a medicolegal setting (Hummel et al., 1999). With the development of olfactory sciences and the field of aromachology, health implications that may arise from targeted stimulation of the retronasal olfactory pathway have come into the forefront of research.